METHODS FOR LOCAL CHANGES IN THE PLASTIC DEFORMATION DIAGNOSTICS ON THE WORK FUNCTION - K. V. Panteleyev; A. I. Svistun; A. L. Zharin (Приборы и методы измерений, 2015)
The paper describes the electronic work function measurements by the contact potential difference technique, and experimental demonstration of the possibility of these methods application for the stress-strain state of the surface layer of the metals and alloys. The techniques end examples of their application of localization of plastic deformation studies using the Kelvin probe are developed and present. The study topology of work function the deformed surface possible to determine the type of deformation and dynamics of